Influence of Phyllanthus emblica Extract Fortified Mulberry Leaves on the Commercial Parameters of the Silkworm Bombyx mori. L - Naphade, S. R.; Chavan, R. J.; Hiware, C.J. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
In recent years, a variety of plant extracts in varying concentrations have been utilized in commercial silk farming to observed their effects on commercial parameters of Bombyx mori L. In the present investigation, the effects of ethanolic extract of Phyllanthus emblica Linn. was studied with different concentrations on the larvae of silkworm, Bombyx mori L. The results show increasing trend in some important commercial parameters. The effective increase in single cocoon weight, filament length and filament weight was observed with the use of 1: 2, 1: 4 and 1: 8 concentrations of Phyllanthus emblica Linn.